Emotional intelligence, conflict resolution skills as correlates of marital stability among couples in Lagos State, Nigeria (2010)
This study was conducted to find out how emotional intelligence and conflict resolution skills predict marital stability among married couples. The sample for this study consists of two hundred and fifty (250) marriage couples (males and females) in Lagos. The research instrument used was a validated questionnaire to measure the independent and dependent variables of the study. Four (4) hypotheses were tested, at 0.05 level of significance using Pearson correlation analysis and i-test statistics. The findings revealed that emotional intelligence had significant relationship with marital stability (r = .537, P<.0.05). There is significant relationship between conflict resolution skills and marital stability (r = .562 P<0.05). There was no significant difference in the conflict resolution skills of married males and their female counterparts (t = 1.106, P>0.05). Based on these findings, government should spearhead organization of seminars for married couples. Potential couples and married couples should also be exposed to emotional intelligence and conflict resolution skills' training